Formulation and characterization of ginger-loaded niosome - Bagheri, Ali (2013)
Ginger oil is well known for its potential as a bioactive phytochemical and long history of medicinal use with antioxidant, anti-obesity and cancer preventive activity. Although many herbal drugs have potential to promote health in vitro findings they have shown less or no in vivo actions due to their poor solubility or improper molecular size or both, ultimately resulting in poor bioavailability and poor absorption which are the major limiting factors of development herbal drugs. Niosome as a lipid-based carrier system with remarkable advantages over conventional drug delivery systems was used as a carrier in this study in order to get the benefits of both herb and carrier. Therefore, the main objective of this study was to formulate the ginger oil-loaded niosome. Firstly, pre-formulation studies were carried out in order to investigate the feasibility of encapsulation ginger oil as a lipophilic active compound. All niosome formulations were prepared by the film hydration method and characterized for drug entrapment efficiency (EE) and particle size (PS). Niosome formulations were optimized with using Response Surface Methodology (RSM) based on Central Composite Design (CCRD). Interaction of two formulation variables, namely amount of Span 60 (x1) and Labrasol (x2) which have great influence on particle size and entrapment efficiency were studied. Labrasol was determined as a key factor responsible for entrapment efficiency which increasing concentration of Labrasol from 0.45 (mM) to 2.5 (mM) has decreased around 10 % of entrapped drug. In conclusion, the niosomes were successfully able to encapsulate ginger oil with high entrapment efficiency which can be useful in developing more effective use of ginger oil for human health.